2015
DOI: 10.1111/ajt.12970
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Biliary Complication Rates Following Liver Transplantation: Implications for Cost and Outcome

Abstract: Although biliary complications (BCs) have a significant impact on the outcome of liver transplantation (LT), variation in BC rates among transplant centers has not been previously analyzed. BC rate, LT outcome and spending were assessed using linked Scientific Registry of Transplant Recipients and Medicare claims (n ¼ 16 286 LTs). Transplant centers were assigned to BC quartiles based upon risk-adjusted observed to expected (O:E) ratio of BC separately for donation after brain death (DBD) and donation after ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 41 publications
2
33
1
Order By: Relevance
“…This is not in concordance with previous literature, where biliary complications are alleged to have a negative impact on graft and overall survival after liver transplantation [22]. This might be explained by the fact, that the majority of patients with BC in this were treated endoscopically and if successful, survival after liver transplantation was equal to patients without biliary complications.…”
Section: Discussioncontrasting
confidence: 82%
“…This is not in concordance with previous literature, where biliary complications are alleged to have a negative impact on graft and overall survival after liver transplantation [22]. This might be explained by the fact, that the majority of patients with BC in this were treated endoscopically and if successful, survival after liver transplantation was equal to patients without biliary complications.…”
Section: Discussioncontrasting
confidence: 82%
“…The use of grafts from marginal donors and elderly donors has steadily increased during recent years, 9,13 leading to higher risk of developing ITBLs. Donor age is particularly high in Germany (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that post‐transplant complications are likely associated with increasing cost in both children and adults . In a pediatric single‐institution study, a multivariate analysis demonstrated increased LOS and total cost in children with HAT following liver transplantation .…”
Section: Discussionmentioning
confidence: 99%